สารสำคัญที่มีฤทธิ์ลดรอยคล้ำรอบดวงตาและถุงใต้ตาในผลิตภัณฑ์เครื่องสำอาง (ANTI-DARK CIRCLE EYE AND ANTI-BAG EYE ACTIVE INGREDIENTS IN COSMETIC PRODUCTS) - Subongkot, Thirapit (Thai Bulletin of Pharmaceutical Sciences, 2017)
ผิวหนังบริเวณรอบดวงตามีความบางมากกว่าบริเวณอื่นของร่างกาย ทำให้เกิดการเปลี่ยนแปลงของสีผิวได้ง่าย รอยคล้ำรอบดวงตาเกิดขึ้นได้จากหลายสาเหตุ เช่น จากการสะสมของรงควัตถุ ได้แก่ ฮีม บิลิรูบิน และธาตุเหล็กในชั้นผิวหนัง โดยรงควัตถุเหล่านี้เกิดจากการสลายตัวของฮีโมโกลบินในเม็ดเลือดแดงภายหลังจากที่มีการรั่วออกนอกหลอดเลือด รอยคล้ำรอบดวงตายังสามารถเกิดจากความผิดปกติของการสังเคราะห์เมลานินในผิวหนัง ถุงใต้ตานั้นเกิดจากการสะสมของพลาสมาในผิวหนังซึ่งเป็นผลมาจากการซึมผ่านได้ที่มากขึ้นของหลอดเลือด จึงได้มีการคิดค้นสารสำคัญเพื่อผสมในเครื่องสำอางสำหรับลดรอยคล้ำรอบดวงตา ได้แก่ ไครซิน สารสกัดสาหร่ายทะเล ฟูแคน กาแล็กแทน วิตามินเค และสารสกัดจากพืช โดยมีกลไกการออกฤทธิ์ที่แตกต่างกัน ได้แก่ ไครซินซึ่งสามารถกระตุ้นการสร้างเอนไซม์ที่ใช้สลายบิลิรูบิน สารสกัดสาหร่ายทะเลซึ่งสามารถกระตุ้นการสร้างเอนไซม์ที่ใช้สลายฮีม ฟูแคนและกาแล็กแทนซึ่งสามารถลดการซึมผ่านได้ของหลอดเลือด อย่างไรก็ตามกลไกของวิตามินเคและสารสกัดจากพืชในการลดรอยคล้ำรอบดวงตายังไม่เป็นที่ทราบแน่ชัด ส่วนสารสำคัญที่มีฤทธิ์ลดถุงใต้ตานั้น ได้แก่ เฮสเพอริดินเมทิลชาลโคน อะเซทิลเตตระเพปไทด์-5 และอนุพันธ์ของกรดแกลลิก เฮสเพอริดินเมทิลชาลโคนมีฤทธิ์ลดการซึมผ่านได้ของหลอดเลือด อะเซทิลเตตระเพปไทด์-5 มีฤทธิ์ยับยั้งกระบวนการไกลเคชันและการซึมผ่านได้ของหลอดเลือด ในขณะที่อนุพันธ์ของกรดแกลลิกออกฤทธ์โดยการกระตุ้นการไหลเวียนของน้ำเหลือง จากการทดสอบประสิทธิภาพของผลิตภัณฑ์ที่ผสมสารสำคัญดังกล่าวในอาสาสมัคร พบว่าสามารถลดรอยคล้ำรอบดวงตาและถุงใต้ตาได้ในอาสาสมัครส่วนใหญ่ Since the skin around the eyes is thinner than the others and blood vessels are very fragile, it is susceptible to discoloration. Dark circle eyes result from several causes such as skin accumulation of pigments which are heme, bilirubin and iron. These pigments occurred from hemoglobin degradation of red blood cells after leakage out of blood vessels. Dark circle eyes are also caused by abnormal melanin synthesis in the skin. Eye bag or puffiness results from plasma retention in the skin as a consequence of high permeability of blood vessels. The anti-dark circle eye and anti-bag eye active ingredients with various mechanisms have been developed for cosmetic products. The anti-dark circle eye active ingredients are chrysin, seaweed extract, fucan, galactan, vitamin K and plant extracts. To decrease dark circle eyes, chrysin stimulates bilirubin degradation enzyme while seaweed extract stimulates heme degradation enzyme. Fucan and galactan decrease dark circle eyes by reducing vascular permeability. However, the mechanism of vitamin K and plant extracts in dark circle eye reduction is still unknown. The anti-bag eye active ingredients are hesperidin methyl chalcone, acetyl tetrapeptide-5 and gallic acid derivatives. In order to decrease eye bag, hesperidin methyl chalcone reduces vascular permeability whereas acetyl tetrapeptide-5 inhibits glycation and vascular permeability. Gallic acid derivatives reduce eye puffiness by improving lymphatic circulation. The efficacy tests of anti-dark circle eye and anti-bag eye agents in human volunteers show good outcomes in most subjects.